THE RELATIONSHIP BETWEEN ATTITUDE AND SUPERVISION WITH NURSING DOCUMENTATION COMPLETION IN EMERGENCY DEPARTMENT OF Dr. KARIADI GENERAL HOSPITAL SEMARANG - sapuan, sapuan (Jurnal Keperawatan Malang, 2019)
ABSTRACT Nursing documentation is an important instrument to ensure patient care can be carried out continuously. Quality nursing documentation will guarantee patient safety. Incomplete documentation causes information to be unclear and confusing so that it can cause errors in handling patients. This study aims to determine the relationship between attitudes and supervision with the completeness of nursing documentation at the emergency department of Dr Kariadi Hospital Semarang. The research method used an observational quantitative analytic design with a cross sectional approach. Sampling uses a total sampling technique with a total of 58 nurses. Data was collected using questionnaires and observation sheets. The Spearman test results show that attitudes related to completeness of nursing documentation (p = 0,000; r = 0.706). Supervision relates to completeness of nursing documentation (p = 0,000; r = 0.733). Based on the results of the logistic regression test it is known that attitude is the most dominant variable associated with completeness of nursing documentation (OR = 0.075). Strengthening of nurses themselves in emergency department and hospital management were required for better quality nursing documentation. Keywords: Emergency Department, Nursing Documentation, Attitude, Supervision